2017
DOI: 10.1039/c7sc00289k
|View full text |Cite
|
Sign up to set email alerts
|

Micrometre and nanometre scale patterning of binary polymer brushes, supported lipid bilayers and proteins

Abstract: Binary polymer brush patterns were fabricated using aminosilanes with photo-cleavable protecting groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…It is important to note that we primarily focus on planar substrates; MPBs on curved surfaces and particles have been reviewed previously and provide promising platforms for materials that can be selectively shuttled between phases in multi-component mixtures [55]. Note that there are also so-called "binary" or "ternary" polymer brushes, patterned manually in nanometer-or micron-scales (e.g., using a photomask) on a surface [56][57][58][59][60][61][62][63][64]. We do not consider these as "binary or ternary mixed polymer brushes" here, since their tethered ends are not inherently mixed on a molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that we primarily focus on planar substrates; MPBs on curved surfaces and particles have been reviewed previously and provide promising platforms for materials that can be selectively shuttled between phases in multi-component mixtures [55]. Note that there are also so-called "binary" or "ternary" polymer brushes, patterned manually in nanometer-or micron-scales (e.g., using a photomask) on a surface [56][57][58][59][60][61][62][63][64]. We do not consider these as "binary or ternary mixed polymer brushes" here, since their tethered ends are not inherently mixed on a molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bent and co-workers have exploited alkylphosphonic acid SAMs to protect copper (Cu) and induce area-selective atomic layer deposition (AS-ALD) of inorganic oxides only on silicon dioxide (SiO 2 ) . SAMs can similarly influence the spatial distribution of polymer films through phase separation, , self-assembly, localized brush growth, and thermal dewetting. , However, unlike inorganics, the majority of this past work on SAM-directed polymer thin-film patterning placed SAMs on flat, homogeneous substrates, e.g., with microcontact printing . Developing similar capabilities to selectively pattern polymer thin films on heterogeneous (e.g., metal/dielectric) surfaces would provide fundamental insight that might someday be useful in technological applications.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Garcia et al demonstrated that micro‐ and nanoscale patterns of a POEGMA brush could be created over large areas with high throughput and fidelity using a photolithography technique . Recently, Johnson et al further extended the capability of a photolithography technique to allow for high‐fidelity patterning of a binary polymer brush on a planar surfaces, which could potentially be important for the design of multifunctional surfaces …”
Section: Device‐associated Infectionsmentioning
confidence: 99%